The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/aws2.1326
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and impacts of cyanobacteria in a deep, thermally stratified, oligotrophic lake

Abstract: Cyanobacterial blooms are a concern in oligotrophic lakes because these systems are often used for multiple purposes (i.e., recreation and public water supplies). Monitoring cyanobacteria impacts is challenging in such cases because of low and heterogeneous concentrations over time, space, and depth. Canandaigua Lake (New York State) is oligotrophic, but has been impacted by blooms since at least the early 2000s, with limited quantification. This study integrated data from established shoreline surveillance an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 71 publications
1
2
1
Order By: Relevance
“…However, this does not imply that this pattern will occur every year. For instance, a study recently published on Canandaigua lake, indicates higher water clarity for October 2019 [64] which contradicts from our observations. However, it is important to note that the maps generated in our study are based on a single day and not representative of the monthly average.…”
Section: Spatio-temporal Variation Of Sddcontrasting
confidence: 99%
See 1 more Smart Citation
“…However, this does not imply that this pattern will occur every year. For instance, a study recently published on Canandaigua lake, indicates higher water clarity for October 2019 [64] which contradicts from our observations. However, it is important to note that the maps generated in our study are based on a single day and not representative of the monthly average.…”
Section: Spatio-temporal Variation Of Sddcontrasting
confidence: 99%
“…However, it is important to note that the maps generated in our study are based on a single day and not representative of the monthly average. The authors in [64] do report higher water clarity in June which aligns well with our observations. Whereas the lower water clarity reported in that study is on Aug 22 and Sep 02 for the year 2019.…”
Section: Spatio-temporal Variation Of Sddsupporting
confidence: 93%
“…From a methodological perspective, incorporating cyanobacteria-specific spectral evaluations from satellite remote sensing , presents a promising approach for (re)constructing regional, long-term photochemical data sets at scales challenging for ground-based lake monitoring initiatives such as CSLAP. High-resolution sampling at specific lakes of interest, , on the other hand, should provide a more integrated picture of how transient spatiotemporal heterogeneity and cyanobacterial community succession shape the photoreactivity of DOM. Overall, our work represents a step forward in understanding the implications of cyanobacterial blooms for surface water photoreactivity in the context of a changing climate. , …”
Section: Resultsmentioning
confidence: 99%
“…The study concluded that a combination of rapid bloom identification and effective treatment processes are needed to protect water quality for systems using sources vulnerable to algal blooms. Prestigiacomo et al (2023) conducted an extensive study in Canandaigua Lake, located in the state of New York, to quantify cyano-HABs indicators and understand the role of various factors on the formation and effects of cyano-HABs. Canandaigua Lake is an oligotrophic, thermally stratified lake that in recent years has experienced formation of HABs, which is a great concern since the lake is used for recreational activities and as a source of drinking water supply for thousands of people.…”
Section: Cyanobacterial Presence In Water Sourcesmentioning
confidence: 99%